Analisis At-Tamanni dalam Q.S Al-Fajr Ayat 24 : (Studi Analisis Tinjauan Ilmu Balaghah) - Cikal Awandano; Ifrohul Fadhilah; Widya Kartika; Harun Al Rasyid (STIKes Ibnu Sina Ajibarang, 2024)
This research paper attempts to fundamentally review At-Tamanni's dictions contained in the Qur'an. The author will give a special analysis to Surah Al-Fajr verse 24 which tells about someone who regrets and wishes he wanted to return to a previous incident. The method used in this paper is the method of data collection. To perfect this article, the author refers to several credible literature such as the Ulumul Qur'an, journal papers, and online articles. This research succeeded in finding that by using the diction